Hubungan Antara Asupan Makanan dan Tingkat Pengetahuan Ibu Hamil dengan Kejadian Kurang Energi Kronik (KEK) dalam Upaya Pencegahan Stunting - Nurdewi Sulymbona; Marwah Aisyah S; Usnal Aini; Tia Srimulyawati (Jurnal Sains & Kesehatan, 2026)
Indonesia is one of the countries that ratified the Sustainable Development Goals (SDGs) as a global agreement. One of the second SDGs is improving nutrition. Chronic Energy Deficiency (CED) in pregnant women is a nutritional problem that is still quite high in Indonesia and contributes to the increased risk of pregnancy complications, low birth weight babies, maternal and infant mortality, and even the risk of stunting. The prevalence of CED pregnant women in Indonesia was 9.7% in 2020, 8.7% in 2021, 8.56% in 2022, and 9.6% in 2023. The purpose of this study was to determine the relationship between food intake and the level of knowledge of pregnant women with the incidence of CED in stunting prevention efforts. This study used a cross-sectional study approach. The sampling technique used total sampling with a sample size of 61 respondents, using Spearman's rank analysis. The results of the Spearmens rank statistical test showed that there was a relationship between food intake and the incidence of chronic energy deficiency (CED) with a value (p-value = 0.001) and there was a relationship between the level of knowledge and the incidence of chronic energy deficiency (CED) with a value (p-value = 0.031). The conclusion of this study is that there is a relationship between food intake and the level of knowledge of pregnant women with the incidence of chronic energy deficiency (CED) in efforts to prevent stunting in the working area of ​​the Kumbewaha Health Center in 2025. Suggestions for pregnant women are to increase their knowledge about food intake during pregnancy to avoid CED.